Kahoot Gamification as a Strategy for Internalizing Pancasila Values for Arabic Language Education Students - Komaruddin Komaruddin; Muh. Wasith Achadi; Adhi Setiyawan (Al Qalam: Jurnal Ilmiah Keagamaan dan Kemasyarakatan, 2026)
Pancasila education is often delivered through textual and didactic approaches, which tend to limit active student engagement. This study aims to analyze how Kahoot-based gamification facilitates the internalization of Pancasila values among students of the Arabic Language Education Department at UIN Sunan Kalijaga Yogyakarta. Therefore, this study employs a qualitative case study design to explore students' learning experiences during gamified instruction. Data were collected through participatory observation, in-depth interviews, and documentation, and were analyzed using data reduction, data display, and conclusion drawing techniques. The findings indicate that Kahoot gamification successfully creates a more interactive, competitive, and collaborative learning environment. Students demonstrated increased intrinsic motivation, marked by spontaneous reactions, increased focus, and consistent engagement throughout the activity. Their understanding of Pancasila values improved through application-based questions that encouraged them to connect concepts with real-life contexts. Gamification also fostered digital civic engagement, reflected in students' sportsmanship, honesty, and adherence to game rules. The lecturer's role as a facilitator was crucial in balancing enjoyment with meaningful value reflection. Although some technical challenges occurred, such as unstable internet connections, these issues did not significantly hinder the learning process.